2023
DOI: 10.1039/d3cb00052d
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal ions and neurotransmitters: coordination chemistry and implications for neurodegeneration

Abstract: Neurodegeneration is characterized by a disturbance in neurotransmitter-mediated signaling pathways. Recent studies have highlighted the significant role of transition metal ions, including Cu(I/II), Zn(II), and Fe(II/III), in neurotransmission, thereby making...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…The literature indicates that these pathological processes involve the contribution of metal ions [ 33 ]. Research has shown that transition metal ions, specifically Cu(I/II), Zn(II), and Fe(II/III), play a significant role in neuro-transmission [ 34 ]. This finding further emphasizes the importance of research in this area and highlights the potential for metal ions to be used as a therapeutic target in the development of drugs for neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…The literature indicates that these pathological processes involve the contribution of metal ions [ 33 ]. Research has shown that transition metal ions, specifically Cu(I/II), Zn(II), and Fe(II/III), play a significant role in neuro-transmission [ 34 ]. This finding further emphasizes the importance of research in this area and highlights the potential for metal ions to be used as a therapeutic target in the development of drugs for neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…140–142 Such structural transformations could further lead to aggregation or polymerization, ultimately causing their loss of function. 143…”
Section: Copper-related Toxicity Mechanismsmentioning
confidence: 99%
“…Metal ions, M n + , play a fundamental role in neurochemistry. While some alkaline and alkaline earth metal ions are essential for the proper regulation of neurotransmitter (NT) release and uptake, the interference of most other cations is detrimental and thought to trigger neurodegenerative diseases. Generally, this effect of metal ions on NTs is only indirect by binding to proteins gating NT transport.…”
Section: Introductionmentioning
confidence: 99%